THE INFLUENCE OF PARENTING AND LEARNING STYLES ON CLASS XI AND XII ACHIEVEMENT IN FINANCIAL ACCOUNTING AND INSTITUTIONS ON GOVERNMENT ACCOUNTING SUBJECTS VOCATIONAL HIGH SCHOOL 6 JAKARTA - Putri, Dara Anggraeni Bimanyu; Zulaihati, Sri; Sumiati, Ati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2020)
This study aims to determine the effect of parenting and Learning Style on learning achievement class XIand XII AKL on Government Accounting subjects. at SMK Negeri 6 Jakarta. This research was conductedfor 4 months starting from April to July 2020. The research population was 83 students of class XI andXII of SMK Negeri 6 Jakarta majoring in Financial Accounting and Institutions. The sampling techniqueuses saturated sampling so that a sample of 83 students is obtained. Variabel Data LearningAchievement obtained from final semester exam (UAS) scores in Government Accounting subjects,Parenting Parents, and Learning Styles obtained from questionnaires.